Elemental analysis of limestone by laser-induced breakdown spectroscopy, scanning electron microscopy coupled with energy dispersive x-ray spectroscopy and electron probe microanalysis. (17th October 2018) - Fahad, Muhammad; Farooq, Zahid; Abrar, Muhammad; Shah, Khizar Hussain; Iqbal, Tahir; Saeed, Sundas
Abstract: Limestone, a sedimentary rock-forming mineral is a source of lime and is important industrially as it usually contains  +95% calcium carbonate and  <5% impurities. The presence of these impurities can cause problems while accessing the different applications of limestone requiring high chemical purity. Due to its great significance and multiple applications, the qualitative and quantitative analysis of limestone is highly desirable. The analysis of the emission spectrum obtained at the fundamental harmonic (1064 nm) of Q-switched Nd:YAG laser revealed the presence of Ca, Si, Al, Mg, Na, Fe, Ti, K, Sr and S with varying intensities. The Boltzmann plot method used to deduce the excitation temperature, and the electron number density value measured by the Stark broadening method resulted in the ranges from 4091–4231 K and (1.2–6.4)  ×  10 16 cm −3, respectively. The quantitative analysis has been performed using the calibration-free laser-induced breakdown spectroscopy (CF-LIBS) technique based on the assumption of local thermodynamic equilibrium and optically thin plasma. The results of the CF-LIBS technique were compared to the measurements of other more standard analytical methods such as scanning electron microscopy coupled with energy dispersive x-ray spectroscopy and electron probe microanalysis with good agreement.